Pengembangan Kultur Mikrospora pada Varietas Padi Ladang Lokal Asal Kendari - Suaib, ,; Arma, Makmur Jaya (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2012)
The three Kendari local upland rice varieties i.e. Paedai Meeto, Pae Ikulaku and Pae Loio were studied for their ability to produce the embryogenic microspore and microspore callus from anther under high temperature stress pretreatments. The pretreatment was conducted by incubating the anther in a B medium at 33 oC in darkness for 0, 2, 4, and 7 days to induce the growth of embryogenic microspores. The formation of microspore calli was obtained by incubating the embryogenic microspores into the MO-19 embryo induction medium. Scoring was conducted on the percentage of: (1) embryogenic microspores, (2) symmetrical binucleat microspores, (3) multinucleate microspores, and (4) microspore calli or embryos. Each replication consisted of three hundred of individual microspores and every treatment was replicated in three times. The mean values of the data were analyzed by variance analysis, and the Fisher LSD mean separation at 0.05 of significance level were applied to judge the best treatments. The result showed that Pae Loio produced the higher frequency of embryogenic microspores after anther pretreatment in B medium for 4 days at 33 oC in darkness compared to other varieties. Culture of embryogenic microspore of Pae Loio in MO-19 medium over 30 days also produced the symmetrical binucleate and multinucleate microspores, and microspore calli at higher frequencies than those of other local varieties.Keywords: anther, calli, embryogenic microspores, high temperature pretreatment, upland rice